GIS-Based Visualization of Lightning Activities in Peninsular Malaysia and Its Correlation With Monsoon Seasons - Ahmad N.A.; Kadir M.Z.A.A.; Ya N.N.C.; Amirulddin U.A.U.; Roslan N. (VDE Verlag GmbH, 2025)
The paper presents a method for visualizing lightning occurrence maps using three years of data in Peninsular Malaysia from 2017 to 2019. The lightning occurrence maps were made to understand lightning distribution patterns and determine the high-activity regions. This was accomplished using advanced Geographic Information System (GIS) software combined with an in-depth base map of Peninsular Malaysia with lightning stroke data from Vaisala GLD360. This study has shown the extent to which the lightning occurrence mapping technique works for classifying lightning distribution and determining hotspot locations during monsoon season. The largest total distribution of lightning strikes occurred in May, with 5,157,797 counts (16.5%). The Inter-Monsoon season has the highest average of lightning strokes, occurring in April, May, October, and November with 51.85% within three years. The longest lightning stroke duration occurs between 8 AM and 9 AM with the total amount of average are 293,113 (33.9%). The lightning strokes were evenly scattered throughout the visualization analysis to correspond with the monsoon season's variations these results are important for utility and protection engineers because they may significantly improve the reliability of electrical networks by reducing power outages caused by lightning strokes. ? 2024 IEEE, ? VDE VERLAG GMBH Berlin Offenbach.